Upskilling and the HRD Tripartite Domains for Adult Workers:Using Spiral Dynamic Theory (SDT) - Lisa R. Brown; Mattyna Stephens; Sohelia Sadeghi (Adult Education Research Conference, 2025)
SDT is used to upskill adult workers. This complexity-focused framework for the evolving delivery of AI-facilitated HRD helps assess change dynamics. Its application on three key levels guides adult education.
Keywords: Adult development; collaborative teamwork; problem-solving; self-directed learning; workforce training